CLINICAL AND EPIDEMIOLOGICAL ASPECTS OF RESTRICTIVE/AVOIDANT EATING DISORDERS - Lima , Letícia Vitória do Nascimento (2024)
This is an integrative review of the literature on restrictive/avoidant eating disorders, their clinical and epidemiological aspects, as well as the impact of this condition on the individual's life. This condition is characterized by individuals who exhibit abnormal eating behavior that may or may not lead to weight loss, but which undoubtedly compromises their quality of life. Among the causes suggested for this behavior are patients who do not eat due to fear, neurosensory issues and/or lack of appetite. Diagnostic criteria are used to define the condition, which can coexist with other comorbidities. There is a need for a multidisciplinary team to intervene to improve patients' quality of life, as well as treatment aimed at the various aspects of this disorder.